2005
DOI: 10.1038/sj.npp.1300716
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Dexamethasone Treatment Elicits Sex-Dependent Alterations in Locomotor Activity, Reward-Based Memory and Hippocampal Cholinergic Function in Adolescent and Adult Rats

Abstract: Glucocorticoids are the consensus treatment for preventing respiratory distress syndrome in preterm infants but there is emerging evidence of subsequent neurobehavioral abnormalities, independent of somatic growth effects. Pregnant rats were given 0.2 mg/kg of dexamethasone, a dose commensurate with clinical use, on gestational days 17-19 and behavioral evaluations were made on the offspring in adolescence and adulthood. The dexamethasone groups had the same body weights as the controls but nevertheless displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 63 publications
5
30
0
Order By: Relevance
“…Furthermore, because we examined the entire forebrain, this leaves open the likelihood of missing more focal effects of Dex that may be diluted by the inclusion of large amounts of unaffected subregions. Indeed, we have already identified persistent changes in hippocampal cholinergic indices and related behavioral performance after GD17-19 treatment with 0.2 mg/kg of Dex, a dose that did not elicit detectable changes at the 24 h time point in any of the parameters evaluated here (Kreider et al, 2005). Accordingly, although the present findings indicate a lesser sensitivity to Dex as compared to later developmental stages, these results should not be interpreted as total sparing from the adverse effects of Dex during this period.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, because we examined the entire forebrain, this leaves open the likelihood of missing more focal effects of Dex that may be diluted by the inclusion of large amounts of unaffected subregions. Indeed, we have already identified persistent changes in hippocampal cholinergic indices and related behavioral performance after GD17-19 treatment with 0.2 mg/kg of Dex, a dose that did not elicit detectable changes at the 24 h time point in any of the parameters evaluated here (Kreider et al, 2005). Accordingly, although the present findings indicate a lesser sensitivity to Dex as compared to later developmental stages, these results should not be interpreted as total sparing from the adverse effects of Dex during this period.…”
Section: Discussionmentioning
confidence: 62%
“…Models incorporating stress as a mechanism for increasing circulating glucocorticoids have also proven useful in characterizing neurodevelopmental defects, especially those influencing hypothalamus-pituitary-adrenal axis function (Dean et al, 2001;Felszeghy et al, 2000;Muneoka et al, 1997), but of course, these involve contributions of factors beyond glucocorticoids alone. Nevertheless, several recent studies in rats suggest that glucocorticoids, in doses commensurate with their use in preterm infants, produces lasting alterations in performance, encompassing motor activity, social behaviors, learning, and memory (Benesová and Pavlík, 1989;Kamphuis et al, 2003Kamphuis et al, , 2004Kreider et al, 2005), resembling some of the changes elicited by prenatal stress (Bowman et al, 2004). The current study establishes a cause-and-effect relationship between perinatal Dex treatment in rats and adverse effects on brain development by exploring doses well below (0.05 mg/kg) or within the therapeutic range (0.2 or 0.8 mg/kg), encompassing three different treatment windows that correspond to human neurodevelopment in the second to early third trimester (Dobbing and Sands, 1979;Rodier, 1988), the period in which glucocorticoids are most likely to be administered (Gilstrap et al, 1994): gestational days (GD) 17-19, postnatal days (PN) 1-3 and PN7-9.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, prenatal exposure to dexamethasone or stress (which would increase endogenous adrenal steroids) have been reported to demasculinize or feminize reproductive behaviors in adult male rats (Ward, 1972;Holson et al, 1995). Recent studies have also shown that prenatal dexamethasone treatment eliminated sex differences in locomotor and cognitive behaviors by distinct and often opposite effects in males and females (Kreider et al, 2005). In addition, both pre-and neonatal dexamethasone treatments altered indicies of cell number and size (DNA and protein levels) and synaptic activity in forebrain regions in a sex-and time-dependent manner .…”
Section: Gc Programming Of Midbrain Da Cytoarchitecturementioning
confidence: 99%
“…Hence, we have extended our investigations throughout the rostro-caudal extent of the adult SNc and VTA in order to assess effects on the volume and shape of these regions as well as the size and distribution of the DA populations and the size of the individual perikarya after brief exposure prenatally or neonatally to dexamethasone. The need to study both periods of exposure is governed by the knowledge that different outcomes have been reported for pre-and neonatal GC programming of the neuroendocrine axes governing the stress response and prolactin secretion Owen et al, 2005;Theogaraj et al, 2005;McArthur et al, 2006a) as well as behaviors and indicies of neurotransmitter signaling in the cerebral cortex and hippocampus Kreider et al, 2005;Owen et Moreover, many of these changes are sex-specific, and we have shown that GC programming effects on the DA population size in the hypothalamic arcuate nucleus are restricted to females (McArthur et al, 2006a). Therefore, the present investigations have been carried out in both males and females in order to investigate whether males and females are differentially affected by GC programming effects within the midbrain DA populations.…”
Section: Introductionmentioning
confidence: 99%
“…We recently developed a series of treatment models in the developing rat that take into account the stages of brain development appropriate to the targeted preterm human population, incorporating doses both within the therapeutic range and well below that level (Kreider et al, 2005a(Kreider et al, , b, 2006. Dexamethasone (DEX) treatments in late gestation or the early neonatal period that did not compromise long-term somatic growth, nevertheless disrupted neural cell acquisition, indices of neuritic outgrowth, synaptic activity, and cell signaling involved in trophic regulation of forebrain development (Kreider et al, 2005a), leading to long-term changes in cognition and motor activity (Kreider et al, 2005b), resembling those seen in models of prenatal stress (Bowman et al, 2004;Dean et al, 2001;Felszeghy et al, 2000;Muneoka et al, 1997). This provides strong evidence for a primary effect of glucocorticoids on brain development even at doses below those in clinical use.…”
Section: Introductionmentioning
confidence: 99%